Recovery of image blocks using the method of edge orientation projections - GE Shi-ming; CHENG Yi-min; ZENG Dan; HE Bing-bing (Tongxin xuebao)
In compressed image transmission, channel interference often results in data missing in image blocks. A method was presented based on edge orientation projections for recovery of missing image blocks. The missing block was classified through edge orientation information of the surrounding neighborhood, and was recovered using POCS algorithm by combining frequency and spatial domain information according the class. The proposed method can restore image edge and complex texture satisfactorily. Experimental comparison with RIBMAP shows obvious improvement of the proposed method in restored image quality and robustness.